Valley song - Fugard, Athol (Theatre Communications Group, 1996)
A play which tells a gentle story of how the generations cope with the end of apartheid in South Africa. A young women wants to leave home to begin to lead her own life, but her grandfather takes this as an insult to his way of life and everything he has worked for.